Pengetahuan Penyakit Tidak Menular dan Faktor Risiko Perilaku pada Remaja - Yuliaji Siswanto; Ita Puji Lestari (Universitas Ngudi Waluyo, 2020)
Non-communicable diseases (NCDs) including the most causes of death in the world including Indonesia. Â Adolescence is one of the periods that determine the pattern of formation of health status in adulthood. Risk behaviors generally begin in the teenage period. Risk factors for unhealthy lifestyles in adolescents are caused by many factors, one of which is knowledge. Knowledge or cognitive is a domain that is very influential on a person's actions or behavior. The objective of the study was to assesknowledge about NCDs and behavioural risk factors in adolescents. This research uses descriptive method with cross sectional approach and data collection is done by using a questionnaire. The sample in this study was taken purposively from SMAN 2 Ungaran, SMAN 1 Bergas, and SMA Muhammadiyah Sumowono as many as 146 students. The data obtained were then analyzed using descriptive analysis. The results showed that the most percentage were respondents who had good knowledge about non-communicable diseases that was equal to 46.3%. Nevertheless there are still many respondents who have a fairly good knowledge of 41.8% and as many as 11.0% of respondents still have poor knowledge. Therefore, efforts are needed to increase the knowledge of high school adolescents about non-communicable diseases from schools through collaboration with relevant parties.